Male: the unsung person… boy… men… husband… father… son… / Hafizuddin Md Dali - Md Dali, Hafizuddin (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.